Tumor filoides de mama en paciente embarazada: presentación inusual en práctica obstétrica. Reporte de caso - Johan Pérez García; Guillermo Villagrán Anzueto (Revista Médica Hondureña, 2025)
Introduction: Phyllodes tumor of the breast is a rare fibroepithelial breast neoplasm that represents less than 1% of breast tumors and is even rarer during pregnan-cy. Case description: Patient in the third decade of life, 28 weeks pregnant, with a history of a mass in the left breast for 9 months, which showed rapid growth in recent months. Patient reported a previous history of excision of a simple breast nodule in the same breast. Physical examination re-vealed breast asymmetry, pain that increased in intensity upon palpation. Given the radiological suspicion of BI-RADS 4 C, a biopsy with a Trucut needle was performed, indicat-ing a fibroepithelial tumor and usual ductal hyperplasia with suggestion of resection of the mass to determine the diag-nosis. The case was taken for discussion and with the con-sent of the patient, a simple left mastectomy was performed. Final pathology reported a histopathologically benign phyl-lodes tumor. Conclusion: Diagnosis of phyllodes tumor can be difficult, especially because of easy confusion with breast fibroadenoma. Few cases have been reported in relation to pregnancy, but this case underscores the importance of a multidisciplinary approach to the diagnosis and treatment of breast tumors during pregnancy. Despite the rarity of phyl-lodes tumor in this setting, physicians should consider the possibility of unusual neoplasia, especially in the face of rapid growth of a mass. Highlighting the need to be alert to changes in the characteristics of a breast mass.